2012
DOI: 10.1002/adem.201200049
|View full text |Cite
|
Sign up to set email alerts
|

Uniformly Porous MgTi2O5 with Narrow Pore‐Size Distribution: XAFS Study, Improved In Situ Synthesis, and New In Situ Surface Coating

Abstract: Porous MgTi2O5 ceramics with pseudobrookite‐type structure have been prepared by in situ processing (viz. reactive sintering). In this communication, further studies have been carried out in order to evolve the porous MgTi2O5, viz., (1) X‐ray absorption fine structure (XAFS) study of porous MgTi2O5, (2) improved in situ synthesis (i.e., more precise stoichiometric control), and (3) new “in situ surface coating,” which enables in situ MgTi2O5 synthesis, in situ uniform pore formation, and in situ surface coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Similarly to our previous work [6,7,9], commercially available MgCO 3 (basic) powder (99.9% purity, Kojundo Chemical Laboratory Co. Ltd., Saitama, Japan), TiO 2 anatase powder (99.9% purity, Kojundo Chemical Laboratory Co. Ltd.), and LiF powder (99.9%, Wako Pure Chemical Ind., Ltd, Osaka, Japan) were used as the starting materials. LiF acts as a mineralizer.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly to our previous work [6,7,9], commercially available MgCO 3 (basic) powder (99.9% purity, Kojundo Chemical Laboratory Co. Ltd., Saitama, Japan), TiO 2 anatase powder (99.9% purity, Kojundo Chemical Laboratory Co. Ltd.), and LiF powder (99.9%, Wako Pure Chemical Ind., Ltd, Osaka, Japan) were used as the starting materials. LiF acts as a mineralizer.…”
Section: Methodsmentioning
confidence: 99%
“…Magnesium dititanate (MgTi 2 O 5 ), with pseudobrookite-type structure, also has characteristic unidirectional low-thermal expansion, however, it is less crystallographically anisotropic and more thermally stable than Al 2 TiO 5 [1]. Suzuki et al have recently reported uniformly porous MgTi 2 O 5 ceramics with 3-D network structure [6][7][8][9]. By controlling the stoichiometry and the liquid phase content, idiomorphic MgTi 2 O 5 grains were formed [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly to our previous works [5][6][7][8] O molecules, quantitative analysis of the starting powder was performed by thermogravimetry and differential thermal analysis (TG-DTA). Based on the compositional calibration using TG-DTA data, MgCO 3 (basic) and TiO 2 powders (nominally, Mg:Ti = 1:1, 1:2 and 2:1 in mole fraction) were wet-ball milled in ethanol for 24h.…”
Section: Exerimntalmentioning
confidence: 99%